Secondary Steelmaking - Shamsuddin M. (My University, 2025)
Until the recent past, the mechanical properties and surface quality of steel produced by conventional processes, for example, open hearth, LD, OBM, and so on were up to the satisfaction of consumers in meeting their general requirements. However, in recent years, there has been a steadily increasing demand for better quality steels in terms of lower impurity contents, better surface finish, better internal quality (i.e., inclusion-free), and specific grain size as well as in their mechanical properties in terms of strength, toughness, and workability under extreme forming conditions. In order to fulfill the stringent demand of consumers it has become essential on the part of steel producers to drastically lower down the impurity level in steel, in some cases to a few parts per million. For example, alloy steel forgings, line-pipe steel, and HIC-resistant steel need ultralow sulfur, as low as 0.001% S (10 ppm). It is important to note that secondary treatment reduces the concentration of sulfur, oxygen, nitrogen, hydrogen, and nonmetallic inclusions. Thus, modern steelmaking is classified into two categories: “primary and secondary.” The first category includes the major bulk of steelmaking processes that carry out total refining and melting (if required). In fast (primary steelmaking) processes where operations are completed within 60 min, the resulting steel may not always meet the desired specifications. Hence, the primary steelmaking processes are nowadays restricted to bulk steel production of ordinary quality steels for construction purposes. In order to adhere to the specific composition, molten steel from these units is processed in ladles. This ladle treatment is known as “secondary steelmaking,” which in fact is the second stage of refining that is carried out for the final refining and finishing. By controlling the composition in this way, the deleterious effect of impurities on the mechanical properties is avoided and steel with better internal quality and ultralow carbon/sulfur/phosphorus can be produced. Nowadays, secondary steelmaking units have become an essential part of the integrated steel plants to supply sophisticated grade of steel for continuous casting. In recent years, a large number of research investigations [1–6] have been conducted on secondary refining to produce inclusion-free steels containing ultralow carbon, silicon, and phosphorus. © 2021, The Minerals, Metals & Materials Society.